Un petral de arnés equino altoimperial de Herrera de Pisuerga (Palencia, España) - Illarregui Gómez, E.; Arribas Lobo, Pablo; Pérez González, Cesáreo (My University, 2013)
This contribution presents an element of horse harness used by the roman cavalry, recently discovered at the Herrera de Pisuerga (Palencia, Spain) archaeological dig. Elements of this type are rare and this piece is particularly relevant owing to its state of preservation and archaeological context. It adds to the body of evidence of equine tackle and demonstrates the importance of this military site, which was the headquarters of the "legio IIII Macedonica" and the "ala Parthorum".

Esta contribución presenta un elemento del arnés utilizado por la caballería romana, descubierto recientemente en el conjunto arqueológico de Herrera de Pisuerga (Palencia, España). Los elementos de este tipo son escasos y la singularidad de esta pieza es relevante debido a su estado de conservación y contexto arqueológico. Se suma al conjunto de evidencias conocidas de equipamiento equino, y demuestra la importancia de este yacimiento militar, que fue cuartel general de la "legio III Macedonica" y del "ala Parthorum".
A breastplate from High Imperial equine harness from Herrera de Pisuerga (Palencia, Spain)
Keywords: ODS 11 - Ciudades y comunidades sostenibles; Roman Military Archaeology; Herrera de Pisuerga (Spain); Metalwork; Horse harness